Expression of Ferritin Light Chain (FTL) Is Elevated in Glioblastoma, and FTL Silencing Inhibits Glioblastoma Cell Proliferation via the GADD45/JNK Pathway - Wu, Tingfeng; Li, Yuntao; Liu, Baohui; Zhang, Shenqi; Wu, Liquan; Zhu, Xiaonan; Chen, Qianxue (PLOS ONE, 2016)
Accumulating evidence suggests that iron-associated proteins contribute to tumor initiation and development. Ferritin light chain (FTL), a key protein in iron metabolism, is associated with the survival of glioblastoma multiforme (GBM) patients; however, the molecular mechanisms underlying this association remain largely unclear. Therefore, in the present study, we investigated the role of FTL in the pathogenesis of GBM. By using quantitative real-time RT-PCR, we found that expression of FTL was higher in patients with GBM than in those with low-grade glioma. Immunofluorescence showed that FTL was mainly localized in the nucleus of GBM cells and was closely associated with mitotic spindles. Knockdown of FTL resulted in inhibition of cell growth and activation of the GADD45A/JNK pathway in GBM cells. Immunoblotting revealed that levels of GADD45A protein decreased in GBM cells when FTL expression increased. Furthermore, transfection of GADD45A in GBM cells significantly decreased cell viability, and this effect was impeded by co-transfection of FTL. Moreover, FTL was found to localize with GADD45A in GBM cells, and a coimmunoprecipitation experiment showed that the two proteins physically interacted. Taken together, these results demonstrate a novel mechanism by which FTL regulates the growth of GBM cells via the GADD45/JNK pathway.